2008
DOI: 10.4315/0362-028x-71.10.2129
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Activity of Molds and Their Metabiotic Association with Salmonella in a Model System

Abstract: The aim of this study was to investigate the proteolytic ability of some strains of aspergilli, fusaria, and penicillia and the metabiotic effect of Fusarium oxysporum and Penicillium expansum on Salmonella. The proteolytic activity of the target molds was determined on tomato juice agar and tomato juice, whereas the metabiotic effect of F. oxysporum and P. expansum on Salmonella was assessed in a model system consisting of tryptone soy broth with different amounts of tomato juice added. Fusaria, some aspergil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The proteolytic activity was not affected by the treatment; as the pH of the samples decreased by 0.2-0.3 as reported elsewhere (Cibelli et al, 2008) in the samples where moulds growth was observed (data not shown). Fig.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The proteolytic activity was not affected by the treatment; as the pH of the samples decreased by 0.2-0.3 as reported elsewhere (Cibelli et al, 2008) in the samples where moulds growth was observed (data not shown). Fig.…”
Section: Resultssupporting
confidence: 84%
“…Then, TJ and dTJ samples, inoculated with F. oxysporum, were stored at 25°C for 12 days, evaluating mould contamination on PDA plates and their proteolytic activity through the method of Wade, Vasdinnyej, Deak, and BeuchatL (2003), modified by Cibelli, Ciccarone, Altieri, Bevilacqua, and Sinigaglia (2008).…”
Section: Analysesmentioning
confidence: 99%
“…The presence of L. monocytogenes may be related to the inefficient pasteurization of milk, or defects in the hygiene of the processing environment and equipment used in the manufacture of cheese (GUATEMIM et al, 2016). According to RYSER & MARTH (1987) and CIBELLI et al (2008), L. monocytogenes, E. coli O157:H7 and Salmonella infantis can grow in parallel with increased pH levels in white mold surface-ripened cheeses.…”
Section: Resultsmentioning
confidence: 99%
“…In a preliminary phase, A. fumigatus and E. nidulans showed a proteolytic activity on Gelatine Agar (data not published) and increased the pH of Tomato Agar by 0.45–0.56 unit [20]. Compared to the alkalinizing effect of some fusaria ( F. graminearum , F. avenaceum , F. proliferatum ), the proteolytic activity of the two strains of aspergilli used throughout this research appeared moderate; however, an experiment conducted in a model system (a laboratory medium added with tomato juice) revealed that the increase of the pH of the medium due to the metabolism of a mould ( F. oxysporum ) enhanced signicantly the survival of Salmonella sp.…”
Section: Resultsmentioning
confidence: 99%